Diagnostic value of D-dimer's serum level in Iranian patients with cerebral venous thrombosis - Leila Hashami; Vahid Rakhshan; Hoda Karimian; Mehdi Moghaddasi (MDPI AG, 2016)
Cerebral venous thrombosis (CVT) is a longterm debilitating vascular brain disease with high morbidity and mortality. It may be associated with rise in D-dimer level. The aim of this study was to examine this potential association and identify the critical D-dimer cut-off level corresponding to increase the risk of CVT. This case-control study was conducted on two groups of patients with and without CVT attending the Rasool Akram Hospital (Iran) during 2014 and 2015. D-dimer levels were measured by the rapid sensitive D-dimer assay. Data were analyzed by Spearman's correlation coefficient test, independent-samples t-test, backward-selection multiple linear regression and multiple binary logistic regression analyses. Sensitivity-specificity tests were used to detect D-dimer cut-off for CVT. Differences between the D-dimer levels of the case and control groups were significant (P<0.001). It showed that each level of increase in the number of symptoms could increase the risk of thrombosis occurrence for about 3.5 times. All symptom types except for headache were associated with D-dimer level, while headache has negative association with D-dimer level. D-dimer cut-off point for CVT diagnosis was estimated at 350 ng/mg. We concluded that D-dimer serum level significantly rises in CVT patients. A rounded cut-off point of 350 ng/mg can be used as a diagnostic criterion for CVT prediction.